Medulloblastoblastoma with excessive nodularity: Typical imaging appearance - Win, Myint Tun; Ramli, Norlisah; Mun, Kein Seong (ASEAN Neurological Association, 2017)
Medulloblastoma is the most common form of childhood primary brain tumour arising from the cerebellar vermis. It is classified as WHO grade IV embryonal tumours and currently at least four histological variants have been established. Only few case reports been published on the imaging features of the medulloblastoma with excessive nodularity variant. We report the MRI features of a rare case of medulloblastoma with excessive nodularity in a child which is confirmed by histopathology.